Elderly Male with Ulcus and Diaper Rash Caused by Post-Stroke Immobilization with Hereditary Risk Factors, Uncontrolled Hypertension, Unstable Emotions, and Sleeping Difficulty - Angeline Asti Shiela Permata; Alidha Nur Rakhmani (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2022)
Stroke is the most common cause of death and the third leading cause of disability globally. The incidence is increasing and causing various problems including disease complications, high health costs, and low quality of life. This case report discusses the diagnosis and management as a whole using a family medicine approach to the elderly who experience post-stroke immobilization and its complications. Abstrak Stroke adalah penyebab kematian paling umum dan penyebab kecacatan terbanyak ketiga secara global. Insidennya makin meningkat dan menyebabkan berbagai masalah meliputi komplikasi penyakit, biaya kesehatan yang tinggi, dan kualitas hidup yang rendah. Laporan kasus ini membahas diagnosis dan tatalaksana secara menyeluruh dengan pendekatan ilmu kedokteran keluarga pada lansia yang mengalami imobilisasi post stroke beserta komplikasinya. Kata Kunci: Imobilisasi post stroke, diaper rash, komplikasi, kedokteran keluarga, biopsikososial Dimensions Index : https://app.dimensions.ai/details/publication/pub.1154332711